Diffusion MRI parameters of corpus callosum and corticospinal tract in neonates: Comparison between region-of-interest and whole tract averaged measurements. (September 2018) - Sparrow, Sarah A.; Anblagan, Devasuda; Drake, Amanda J.; Telford, Emma J.; Pataky, Rozalia; Piyasena, Chinthika; Semple, Scott I.; Bastin, Mark E.; Boardman, James P.
Abstract: Purpose: Measures of white matter (WM) microstructure inferred from diffusion magnetic resonance imaging (dMRI) are useful for studying brain development. There is uncertainty about agreement between FA and MD values obtained from region-of-interest (ROI) versus whole tract approaches. We investigated agreement between dMRI measures using ROI and Probabilistic Neighbourhood Tractography (PNT) in genu of corpus callosum (gCC) and corticospinal tracts (CST). Materials and Methods: 81 neonates underwent 64 direction DTI at term equivalent age. FA and MD values were extracted from a 8 mm 3 ROI placed within the gCC, right and left posterior limbs of internal capsule. PNT was used to segment gCC and CSTs to calculate whole tract-averaged FA and MD. Agreement between values obtained by each method was compared using Bland–Altman statistics and Pearson's correlation. Results: Across the 3 tracts the mean difference in FA measured by PNT and ROI ranged between 0.13 and 0.17, and the 95% limits of agreement did not include the possibility of no difference. For MD, the mean difference in values obtained from PNT and ROI ranged between 0.101 and 0.184 mm 2 /s × 10 −3 mm 2 /s: the mean difference in gCC was 0.101 × 10 −3 mm 2 /s with 95% limits of agreement that included the possibility of no difference, but there was significant disagreement in MD values measured in the CSTs. Conclusion: Agreement between dMRI measures of neonatal WM microstructure calculated from ROI and whole tract averaged methods is weak. ROI approaches may not provide sufficient representation of tract microstructure at the level of neural systems in newborns. Highlights: Agreement is poor between dMRI parameters measured in regions of interest within tracts versus whole tract averaged values. ROI approaches may not provide sufficient representation of whole tract microstructure in the developing brain. These observations have implications for the development of neonatal MR image biomarkers.